Optimizing Texture Modified Foods for Oro-pharyngeal Dysphagia: A Difficult but Possible Target? - Sukkar, Samir G.; Maggi, Norbert; Travalca Cupillo, Beatrice; Ruggiero, Carmelina (Frontiers in Nutrition, 2018)
Dysphagia is a swallowing disorder characterized by the difficulty in transferring solid foods and/or liquids from the oral cavity to the stomach, making autonomous and safe oral feeding problematic. The main problems deriving from dysphagia are tracheo-bronchial aspiration, aspiration pneumonia, malnutrition and dehydration. In order to overcome dysphagia-induced problems, over the years water and food thickening has been used, focusing specifically on viscosity increase, but limited results have been obtained. Elastic components and their effects on the cohesiveness on the bolus should be taken into account in the first place. We provide an analysis of the problem suggesting possible corrections to the protocols so far implemented.